CENTRAL SEROUS CHORIORETINOPATHYLIKE MIMICKING MULTIFOCAL VITELLIFORM MACULAR DYSTROPHY: AN OCULAR SIDE EFFECT OF MITOGEN/EXTRACELLULAR SIGNAL–REGULATED KINASE INHIBITORS. Issue Volume 12:Issues 3(2018) (2018) - Giuffrè, Chiara; Miserocchi, Elisabetta; Modorati, Giulio; Carnevali, Adriano; Marchese, Alessandro; Querques, Lea; Querques, Giuseppe; Bandello, Francesco
Abstract : Purpose: To describe a case of multiple detachments of the neurosensory retina mimicking multifocal vitelliform macular dystrophy after chemotherapy with mitogen/extracellular signal–regulated kinase inhibitor for metastatic ovarian cancer. Methods: Case report. Results: A 38-year-old woman presented to our clinic for eye examination before the initiation of chemotherapy with trametinib. One month after starting treatment, the patient complained of vision loss and metamorphopsia in both eyes. Best-corrected visual acuity decreased from 20/20 at baseline to 20/32 in both eyes, and fundus examination revealed multiple detachments of the neurosensory retina with vitelliformlike appearance, involving the central macula and the posterior pole with a circular distribution along the retinal vascular arcades. Spectral-domain optical coherence tomography showed widespread thickening of the interdigitation zone, particularly in areas with and without detachments, and also some hyporeflective fluid accumulating beneath the detached retina. Mitogen/extracellular signal–regulated kinase inhibitor therapy was discontinued, and after 1 week, best-corrected visual acuity recovered to 20/20 bilaterally, with complete resolution of the serous retinal detachments and normalization of interdigitation zone. Conclusion: The development of a central serous chorioretinopathylike retinopathy is a relatively common secondary event of mitogen/extracellular signal–regulated kinase inhibitors therapy, and typically, it resolves after the discontinuation of the treatment. Our case is peculiar in that the lesions were bilateral, involving the central macula and the posterior pole with a circular distribution along the retinal vascular arcades and in that the interdigitation zone showed a widespread thickening at spectral-domain optical coherence tomography, mimicking multifocal vitelliform macular dystrophy. Abstract : The development of a central serous chorioretinopathylike retinopathy is a relatively common secondary event of mitogen/extracellular signal-regulated kinase inhibitors therapy, and typically, it resolves after the discontinuation of the treatment. The authors describe a peculiar case characterized by bilateral lesions, involving the central macula and the posterior pole with a circular distribution along the retinal vascular arcades. In this case, the interdigitation zone showed a widespread thickening, mimicking multifocal vitelliform macular dystrophy.